2009
DOI: 10.1111/j.1468-2354.2009.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of Time and Risk Preferences: Stated Preference Discrete Choice Modeling Analysis Depending on Smoking Behavior*

Abstract: Measuring time and risk preferences and relating them to economic behaviors are important topics in behavioral economics. We developed a new method to simultaneously measure the rate of time preference and the coefficient of risk aversion. Analyzing the individual-level relationships between preference parameters and cigarette smoking, we conclude that current smokers are more impatient and risk-prone than nonsmokers. Heavy smokers are the most impatient and risk-prone, whereas ex-smokers are the most patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 50 publications
0
35
1
Order By: Relevance
“…We conduct a discrete choice experiment (DCE) in a sample of adult tobacco cigarette smokers to help address these information gaps. DCE, a stated preference technique, is increasingly employed by economists to study tobacco‐related products (Buckell, Marti, and Sindelar ; Czoli et al ; Ida and Goto ; Kenkel et al ; Marti , ; Pesko et al ; Regmi et al ; Shang et al ). These methods are grounded in consumer choice theory established by Lancaster ().…”
Section: Introductionmentioning
confidence: 99%
“…We conduct a discrete choice experiment (DCE) in a sample of adult tobacco cigarette smokers to help address these information gaps. DCE, a stated preference technique, is increasingly employed by economists to study tobacco‐related products (Buckell, Marti, and Sindelar ; Czoli et al ; Ida and Goto ; Kenkel et al ; Marti , ; Pesko et al ; Regmi et al ; Shang et al ). These methods are grounded in consumer choice theory established by Lancaster ().…”
Section: Introductionmentioning
confidence: 99%
“…When considering time preferences and their role in smoking (especially with regards to smoking cessation), one should also consider risk aversion, or the likelihood an individual will take on more risk in exchange for the possibility of a larger reward (risk aversion directly affects the concavity of the utility function, see for example Andersen et al 2008). Studies using samples of Japanese individuals have found that lower time discount rates (i.e., more future orientation) and risk aversion predicted quit success significantly (Goto et al 2009;Ida and Goto 2009b). The discrete choice method, in which subjects choose between two different combinations of attributes, allows joint consideration of risk and time preferences and estimation of actual discount rates and risk aversion coefficients.…”
Section: Time Preferences and Smokingmentioning
confidence: 99%
“…Here x n represents variables that capture the availability of government relief, individual flood risk perceptions, experience with floods, insurance purchases, geographical characteristics, and socioeconomic characteristics. The behavioral economics literature indicates that individuals can react in very different ways to probabilistic information (e.g., Ida and Goto, 2009). This is examined by specifying the coefficient of the probability variable as random, using the mixed logit model.…”
mentioning
confidence: 99%